THE RELATIONSHIP BETWEEN SPORTS FACILITY SERVICE QUALITY AND CUSTOMER SATISFACTION OF GOR SAPARUA - Kurniawan, Muhamad Rachmaan; Saputra, Yudha Munajat; Kusmaedi, Nurlan (UNIVERSITAS NEGERI MAKASSAR, 2021)
Public service is a government obligation in fulfilling the rights of every citizen. To facilitate the delivery of government services to the community, a public service model is needed. One of them in public service is sports. Of course, sports play an important role in the development of human life. Public sports facilities have played a very important role in promoting physical activity and participation in recreational sports activities. Therefore, there are significant efforts to continuously improve the image of recreational sports and to pursue the improvement of the service quality of public sports facilities. Several dimensions can be measured to determine service quality on customer satisfaction, including tangibility, reliability, assurance, responsiveness, and empathy. This study aims to determine whether there is a relationship between service quality and customer satisfaction who visits Saparua Sports Hall, Bandung City. This type of research is correlational and the method used is quantitative with an accidental sampling technique with a sample size of 100 respondents. The overall result of the study is that there is a relationship between service quality and customer satisfaction who visits Saparua Sports Hall.